Fisheries and Aquaculture Production in Reservoirs in Lao PDR - Saphakdy, Bounthong; Phonekampheng, Oudom; Bouapao, Lilao; Hortle, Kent (CGIAR Challenge Program on Water and Food, 2013)
The project’s overall aim is to provide better information on reservoir fisheries and aquaculture so that reservoirs will be planned and managed to provide a broader range of benefits, particularly to rural people living nearby. Some specific questions which the project is addressing include the following.